Development of a Skills-Based IPC Supervisor Course During the 2018-19 DRC Ebola Virus Disease Outbreak. (October 2020) - Wilson, Katie; Gomes, Danica; Mangala, Samuel; Osuka, Hanako; Umeakunne, Erica Tindall; Hazim, Carmen; Patrick, Molly; Dennison, Cori; Herzig, Carolyn; Baller, April; Cihambanya, Landry; Padoveze, Maria Clara; et al.
Abstract : Background: With >3, 000 cases and 2, 000 deaths, the current outbreak of Ebola virus disease (EVD) in the Democratic Republic of the Congo (DRC) is the second-largest reported EVD outbreak in history. Healthcare-associated transmission of EVD has been a persistent amplifier of transmission due, in part, to fragility of the healthcare system, lack of basic infection prevention and control (IPC) infrastructure, and large number of healthcare facilities (HCFs). A central component of the strategy to rapidly strengthen IPC in HCFs is the provision of IPC supervisors to oversee standardized risk assessments and improvements and provide mentorship to HCF staff. To support these activities, we designed skills based training for IPC supervisors. Methods: Staff recruited by the Ministry of Health (MoH) to strengthen IPC are part of an outbreak-specific cadre known as IPC supervisors. IPC supervisors, who originally lacked technical knowledge and mentoring experience, were trained to provide technical support and mentorship to staff at HCFs, with the objective of improving IPC-related processes and behaviors. A competency-based training course was designed by conducting informal assessments of IPC supervisors during daily tasks to identify areas for performance improvement. We developed competencies based on activities designated for IPC supervisors according to MoH guidelines. We planned an iterative training rollout to allow for continuous, real-time modifications based on lessons learned throughout the implementation phase. Results: Although IPC supervisors displayed technical knowledge of IPC recommendations, we observed large gaps in implementation. IPC supervisors frequently failed to recognize behaviors that are high-risk for infection transmission. In addition, IPC supervisors lacked the ability to develop prioritized action plans and to implement interventions aimed at rapidly improving IPC practices. The course, designed as an interactive, skills-based training, is rooted in instructional design principles and addresses 4 key competencies: risk recognition and prioritization, IPC assessment completion, action plan development, and effective leadership and communication. The course will be pilot tested in the DRC to an audience of 25 IPC supervisors. Conclusions: In an outbreak setting, strong mentorship and problem-solving skills are needed to support effective implementation of IPC quality improvement. Trainings that are informed by field experiences and teach problem-solving, coaching, and communication skills are critical and can be developed rapidly. The strategy employed by the Ministry of Health to rapidly achieve IPC capacitation at HCFs might be adapted for use in future outbreaks. Funding: None Disclosures: None